Estrategias de marketing digital para la promoción turística de los recursos arquitectónicos patrimoniales de la ciudad de Portoviejo - Intriago Intriago, Melania Jamileth (2023)
The present study was carried out in Portoviejo city, Manabí province, with the purpose of establishing digital marketing strategies for the tourist promotion of the patrimonial architectural resources of the city. Its development began with the diagnosis of the current situation in Portoviejo's architectural resources, in order to build a tourism baseline through the characterization of the resources and tourism management of the city. Then, the tourist/visitor profile and their motivations for architectural tourism in Portoviejo city were identified. Finally, a proposal was made with digital marketing strategies, as an instrument for the tourist dissemination of the architectural resources of the city, which was validated and approved through the expert method. As a result, it was obtained that the tourism dissemination strategies will be carried out in agreement with the MINTUR, through the website and social networks of the GAD; in addition, it was learned that the cantonal GAD develops a planning process called PLAN 2035, in order to strengthen the tourist promotion of the architectural attractions of the city. It is concluded that, among the strategies most used in Portoviejo for tourism promotion, are digital media such as: Facebook (40%), WhatsApp (30%), digital press (20%) and Twitter (10%).